(untitled) (Submission and Review of Research -Biological Sciences Series, 2025)
The present study was conducted to demonstrate the adverse effects of acetamiprid, a neonicotinoid insecticide widely used as a substitute for organophosphates and carbamates, by examining histopathological changes. The study included 30 pregnant mice, randomly divided into three groups, and administered specific doses of the insecticide orally for 10 consecutive days. The first group served as a control, while the second group received a daily oral dose of 31 mg/kg of acetamiprid. The third group was administered a daily oral dose of 50 mg/kg. The findings revealed that acetamiprid induced liver damage, including lymphocytic infiltration, congestion of the central vein, mild bilirubin pigment accumulation, necrotic foci, and severe degenerative changes. These pathological alterations are attributed to oxidative stress caused by the release of free radicals and the liver cells’ inability to repair and mount effective antioxidant defenses.